Regional Gene Expression of Inflammation and Oxidative Stress Responses Does Not Predict Neurodegeneration in Aging. Issue 2 (23rd January 2017) - López-González, Irene; Tebé Cordomí, Cristian; Ferrer, Isidro
Abstract : Brain aging is accompanied by increased oxidative stress and what has been termed "neuroinflammation, " which might contribute to age-related neurodegenerative diseases. We analyzed expression in the transcription of innate inflammatory response genes in eleven representative regions including frontal, parietal, inferior temporal, cingulate, occipital, entorhinal cortex, caudate, putamen, thalamus, substantia nigra, and cerebellar vermis in aging human brains. We probed members of the complement system, colony stimulating factor receptors, toll-like receptors, and pro- and anti-inflammatory cytokines in the brains of subjects with no neurological disease and neurofibrillary tangles (mean age: 47.1 ± 5.7 years) and those with no neurological disease and neurofibrillary pathology stages I–II (mean age: 70.6 ± 6.3 years). Although the entorhinal and frontal cortex were most altered, gene regulation patterns did not match regions with increased vulnerability. Analysis of false discovery rate thresholds revealed no differences for any gene in any region between the 2 groups, including cases in which individual comparisons analyzed using Student t or nonparametric tests showed apparent differences between groups. Moreover, gene expression of major anti-oxidative stress responses did not match neuroinflammation in aging or increased regional susceptibility to major neurodegenerative diseases.